CHARGING CAR RENTAL COSTS DURING POST-ACCIDENT REPAIR PERIOD FROM WAHBAH AZ-ZUHAILI'S PERSPECTIVE (CASE STUDY OF CAR RENTAL COMPANIES IN MEDAN TEMBUNG) - Afrison Ardanis Siregar; Sahliah Sahliah (Program Pascasarjana UIN Sumatera Utara, 2025)
This study explores the imposition of car rental fees during post-accident repair periods from the perspective of Wahbah Az-Zuhaili, with a focus on car rental companies operating in Medan Tembung. The primary objective is to examine the risk-sharing arrangements between the renter and the vehicle owner, as well as the consequences arising from accidents involving rented vehicles. The study further analyzes the compatibility of the risk coverage system implemented by rental companies with the principles of the ijarah ‘ala al-manfa'ah contract, as interpreted by Wahbah Az-Zuhaili. A qualitative research method with a normative-empirical analysis approach was employed. The findings reveal that rental companies, specifically Zahri Rental, place full liability on renters for vehicle damages even when not caused by renter negligence. Renters are also required to pay additional rental fees while the vehicle is under insurance repair, despite having already covered the insurance claim. This policy is driven by the substantial financial losses incurred by Zahri Rental due to idle vehicles that cannot be rented out during repairs. Although intended to mitigate company losses, this practice does not fully align with the principles of ijarah ‘ala al-manfa'ah, which emphasize a balanced benefit between the renter and the rental owner.